Electromagnetic Field and Radiation of Charged Particles in the Vicinity of Schwarzschild Black Hole - Stanislav Komarov; Gregory Vereshchagin (Particles)
We provide a concise review of the problem of calculating the electromagnetic field and radiation of a charged particle in the vicinity of a black hole. The interest in this problem has been revived due to recent progress in multimessenger observations. Many astrophysical models of energy extraction from a black hole involve consideration of such motion and radiation. Our main goal is to highlight the basic assumptions and limitations of various techniques and point out the main conclusions of these studies.